Pemodelan Parameter a Pada Hidrograf Satuan Sintetik Nakayasu (Studi Banding Dengan Hidrograf Satuan Sintetik Gama 1) - M Ramadani; Manyuk Fauzi; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Choosen of hydrograph parameter  (α)  on hydrograph synthetic of Nakayasu is subjective depends on raising and recession of the hydrograph’s arc and often got problem on choosen hydrograph parameter (α). The research aims are to determine equation of α (alpha) on hydrograph synthetic of Nakayasu method, and also to analyse effect of river characteristics on α based on volume control. Results show that long of watershed and area of watershed were influenced equation of α..Calculation produce